2023
DOI: 10.3390/nu15163622
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Studies on the Supplementation of Manufactured Human Milk Oligosaccharides: A Systematic Review

Yannik Bernd Schönknecht,
María Virginia Moreno Tovar,
Stina Rikke Jensen
et al.

Abstract: Human milk oligosaccharides (HMOs) are a major component of human milk. They are associated with multiple health benefits and are manufactured on a large scale for their addition to different food products. In this systematic review, we evaluate the health outcomes of published clinical trials involving the supplementation of manufactured HMOs. We screened the PubMed database and Cochrane Library, identifying 26 relevant clinical trials and five publications describing follow-up studies. The clinical trials va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Another class of components studied were HMOs. It has been demonstrated that supplementing infant formula with HMOs (in particular with 2'-FL), the composition and effects of the formula become similar to those of breast milk (better growth, reduced number of respiratory infections, better gut microbiome composition, reduced plasma levels of proinflammatory cytokines), 37 but no clinical study has so far demonstrated a direct effect on neurocognitive development, although this can be presumed from preclinical studies (improved neuronal connectivity, long-term memory and potentiation). 21 Until now, only one study analysed the effect of HMO supplementation on preterm infants: Hascoët et al 38 conducted an RCT which included 86 preterm and VLBW infants (43 received HMO supplement with 2'-FL and lacto-N-neotetraose; 43 received glucose-based placebo) and reported a significant better growth in length and head circumference in the HM group.…”
Section: Hm Fortificationmentioning
confidence: 99%
“…Another class of components studied were HMOs. It has been demonstrated that supplementing infant formula with HMOs (in particular with 2'-FL), the composition and effects of the formula become similar to those of breast milk (better growth, reduced number of respiratory infections, better gut microbiome composition, reduced plasma levels of proinflammatory cytokines), 37 but no clinical study has so far demonstrated a direct effect on neurocognitive development, although this can be presumed from preclinical studies (improved neuronal connectivity, long-term memory and potentiation). 21 Until now, only one study analysed the effect of HMO supplementation on preterm infants: Hascoët et al 38 conducted an RCT which included 86 preterm and VLBW infants (43 received HMO supplement with 2'-FL and lacto-N-neotetraose; 43 received glucose-based placebo) and reported a significant better growth in length and head circumference in the HM group.…”
Section: Hm Fortificationmentioning
confidence: 99%
“…In a recent publication (Schönknecht et al., 2023), a systematic review evaluated the health outcomes of 26 published clinical trials performed with HiMOs. A total of eight different HiMO alone or in mixtures at different dose levels in comparison with standard IF and/or breastfed infants were evaluated.…”
Section: Assessmentmentioning
confidence: 99%
“…However, the findings are variable, and the results are not consistent across all studies. Moreover, formula-randomized controlled trials and real-world studies have not shown added growth benefits among those receiving supplementation with select HMOs [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%